Event-triggered communication scheme for stochastic systems in wireless sensor networks. (February 2020) - Xiaoyan, Sun; Yi, Gao; Quansheng, Liu
With the development of sensors and network technology, wireless sensor networks are widely used in various scenes. However, in most applications, the energy of the sensor nodes cannot be supplemented. In addition, since the lifetime of the electronic switching element is measured by the number of trigger times, which makes the effective use of energy, extending the working life of the network becomes one of the key factors to be considered. This paper discusses an event-triggered control scheme for stochastic systems. The mechanism determines when the controller sends control data in order to balance system performance and drive frequency. In this paper, the control scheme is deduced by a class of quadratic performance index function. Then, the formula of performance index is designed based on state feedback and output feedback, and the upper bound of performance index is deduced and the conditions in the theorem can be constructed by solving a set of linear matrix inequalities, which can be easily tested with linear matrix inequality algorithms. Finally, a numerical example is given to illustrate the results.